Determination of Adoption of Climate-Smart Agriculture (CSA) Technologies in Rice Production in Using TOPSIS Method (International Journal of Food and Nutritional Sciences, 2019)
With the goal of achieving sustainable agriculture and guaranteeing food security in the faceof climate change, climate-smart agriculture is a method to creating agricultural strategies tomodernize agricultural systems utilizing digital tools. This article provides a thoroughassessment of the literature on robots, the Internet of Things, and remote sensing as "smartagricultural technologies" for Cyprus's climate-smart agriculture.